STUDENT VOLUNTEERING: MOTIVATION OF VOLUNTEERS AND SPECIFIC FEATURES OF THEIR ACTIVITY - Mariya V. Pevnaya (Moscow Polytechnic University, 2016)
This paper is devoted to volunteering activity of Russian students. The article presents the results of the monitoring research - survey of the students of economically developed Russian domains - Sverdlovsk region. Students of 14 universities took part in the survey. The author also analyzes some results of survey of young volunteers in Ural. There are some important characteristics of volunteer students' community. Special attention is paid to motivation of student volunteers.